Collaborative Governance Strategy for Impactful Higher Education - Julizar Idris (Annpublisher, 2026)
Background. Higher education transformation drives governance change from an administrative approach to a participatory and collaborative approach. Universities are no longer solely oriented to education and research but are also required to make a real impact on society through innovation, research, and strengthened partnerships. Aims. This research aims to analyze the development of the concept of collaborative governance and its role in supporting the realization of impactful universities. Methods. This study uses a qualitative approach with the Systematic Literature Review (SLR) method. The articles analyzed totaled 200, comprising SINTA and Scopus articles, and were then reduced to 100 based on topic relevance and document completeness. The advanced selection process resulted in 27 articles considered most representative for analysis using thematic analysis techniques. Result. The results show that collaborative governance strengthens multi-stakeholder engagement, improves the quality of decision-making, expands partnership networks, encourages a research culture, and strengthens innovation in higher education. Conclusion. Thus, collaborative governance is an important strategy in realizing impactful and sustainable higher education.